Feasibility study of a field survey to measure antimicrobial usage in humans and animals in the Mekong Delta region of Vietnam - Cuong, NV; Ly, NPC; Van, NTB; Phu, DH; Kiet, BT; Hien, VB; Padungtod, P; Thwaites, G; Choisy, M; Carrique-Mas, J (Oxford University Press, 2021)
Background Development of antimicrobial use (AMU) surveillance systems in humans and animals is a priority for many low- and middle-income countries; however accurate estimations are hampered by a diversity of animal production systems and metrics. The Mekong Delta region of Vietnam is a ‘hotspot’ of antimicrobial resistance and is home to a high density of humans and animal populations.